Centralismo, descentralización y expectativas de la ciudadanía (Conchucos Bajo - Región Áncash) - Vargas Morales, Zenon Eduardo (2008)
This investigation is of essentially exploratory character that it looks for to include/understand the decentralization and the expectations of the citizenship in Conchucos under the Ancash Region. Decentralization that responds to one old aspiration of the country and constitutes one of the main challenges that during both last governments the diverse political forces have assumed like one of the high-priority aspects of the reform of the State. According to the local authorities, the decentralization is means that will allow to reach like objective to share the political power democratically, economic, social and cultural between the different political forces, in each one of the social spaces of the local, regional and national scope. They consider the necessity of an arranged governability that it allows to invigorate the potentialities and thus to be able to reach a sustainable development.